Gender differences in rates of percutaneous coronary intervention, cardiac surgery and valvular disease in indigenous Australians with suspected acute coronary events. (25th November 2020) - Su, H.M.H; Kang, K; Der, Y.S; Millhouse, J.D.S; Seton, N.A; Gederts, S.R; Solayar, R.D; Sartain, F.R; Perrin, E.L; Ramkumar, S; Starmer, G.H
Abstract: Background: Indigenous populations globally have a higher burden of cardiovascular disease and increased mortality after acute coronary events, partly due to inequitable access to specialised care like cardiac catheterisation. Gender differences in revascularisation rates have been well described in non-Indigenous patients. Whether this applies to Indigenous patients when cardiac catheterisation facilities are readily available is unclear. Purpose: We compared the rates of percutaneous coronary intervention (PCI), cardiac surgery, 30-day and long-term all-cause mortality in Indigenous (Aboriginal and Torres Strait Islanders) patients in Far North Queensland (FNQ) – a region with a large Indigenous population and 24/7 cardiac catheterisation facilities. Method: All patients who presented to the tertiary referral center for FNQ, for their first inpatient angiogram between November 2012 and October 2019 were identified. The primary study outcomes were rates of PCI or cardiac surgery and all-cause mortality measured at 30 days and long term. Secondary study outcomes were significant left ventricular dysfunction (ejection fraction <50%) and valvular disease (moderate to severe) in patients who had an echocardiogram. Other differences in baseline characteristics, including age, gender, body mass index, postcode and indication for angiography were accounted for using logistic and cox regression analysis. Results: 1042 patients (mean age 53.7±11.6 years, 45.5% female, median follow-up 1092 days) self-identified as Indigenous. Indigenous women were older 54.8±11.4 vs 52.8±11.7 years, p=0.005 and had different angiography indications. For Indigenous women and men respectively, rates of ST elevation myocardial infarction (STEMI) were 14.6% vs 22.9%, non-STEMI 44.3% vs 46.8%, angina 32.7% vs 21.0%, cardiac arrest 2.7% vs 3.3% and other 5.7% vs 6.0%, p<0.001. Indigenous women had significantly lower rates of PCI or cardiac surgery, 40.5% vs 60.7%, p<0.001, but similar 30-day mortality, 1.5% vs 2.3% p=0.34 and long-term all-cause mortality rates 11.2% vs 10.9%, p=0.89, in unadjusted data. 685 patients (mean age 53.8±11.5 years, 45.5% female) were included in the echocardiogram subgroup. Indigenous women had significantly more valvular disease, 23.3% vs 16.3%, p=0.022 but similar rates of left ventricular dysfunction, 30.2% vs 35.8%, p=0.12. Following adjustment for other baseline characteristics female gender independently predicted lower rates of PCI or cardiac surgery, OR 0.49 (95% CI 0.38–0.64) and higher rates of valvular disease, OR 1.60 (95% CI 1.07–2.39). Rates of ventricular dysfunction, 30-day and long-term all-cause mortality were similar. Conclusions: Indigenous women had significantly different indications for angiography, lower rates of PCI or cardiac surgery and higher rates of clinically significant valvular disease despite presenting in gender ratios similar to the general population in FNQ. Funding Acknowledgement: Type of funding source: None